Expression patterns of an Otx2 and an Otx5 orthologue in the urodele Pleurodeles waltl: implications on the evolutionary relationships between the balancers and cement gland in amphibians. - Sauka-Spengler, T; Germot, A; Shi, D; Mazan, S (2002)
We report the characterization of an Otx2 and an Otx5 orthologue in the urodele Pleurodeles waltl. These two genes, termed PwOtx2 and PwOtx5, share highly conserved expression domains with their gnathostome counterparts at tailbud stages, like the developing forebrain ( PwOtx2), or the embryonic eye and epiphysis ( PwOtx5). As in Xenopus laevis, both are also transcribed in the dorsal lip of the blastopore during gastrulation and in anterior parts of the neural plate during neurulation. In addition, PwOtx5 displays a prominent expression in the developing balancers and the lateral non-neural ectoderm during neurulation, from which they derive. By contrast, PwOtx2 expression remains undetectable in the balancers and their presumptive territory. These data suggest that PwOtx5, but not PwOtx2, may be involved in the differentiation and early specification of balancers. Comparisons of Otx5 expression patterns in P. waltland X. laevis embryos suggest that, as previously shown for Otx2, changes in the regulatory mechanisms controlling Otx5 early expression in the non-neural ectoderm may occur frequently among amphibians. These changes may be related to the rise of cement glands in anurans and of balancers in urodeles. This hypothesis could account for some similarities between the two organs, but does not support a homology relationship between them.